2020
DOI: 10.3389/fphys.2020.589386
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Interactions Between Sodium Channels Provides Insight Into the Negative Dominance of Certain Channel Mutations

Abstract: Background: Na v 1.5 cardiac Na + channel mutations can cause arrhythmogenic syndromes. Some of these mutations exert a dominant negative effect on wild-type channels. Recent studies showed that Na + channels can dimerize, allowing coupled gating. This leads to the hypothesis that allosteric interactions between Na + channels modulate their function and that these interactions may contribute to the negative dominance of certain mutations. Methods: To investigate how allosteric interactions affect microscopic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…An assembly-mediated dominant-GOF mutation for heterozygous G375R can be compared to the well-known dominant-negative effect observed for some types of protein complexes and channelopathies ( Fink et al, 1996 ; Ribera et al, 1996 ; Silberberg et al, 2005 ; Reed et al, 2016 ; Du et al, 2020 ; Hichri et al, 2020 ; Backwell and Marsh, 2022 ). Both can cause disease through a disproportionate fraction of the channels affected.…”
Section: Discussionmentioning
confidence: 99%
“…An assembly-mediated dominant-GOF mutation for heterozygous G375R can be compared to the well-known dominant-negative effect observed for some types of protein complexes and channelopathies ( Fink et al, 1996 ; Ribera et al, 1996 ; Silberberg et al, 2005 ; Reed et al, 2016 ; Du et al, 2020 ; Hichri et al, 2020 ; Backwell and Marsh, 2022 ). Both can cause disease through a disproportionate fraction of the channels affected.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the de novo heterozygous G375R mutation with respect to WT would induce its pathogenicity mainly through a dominant negative effect (31). Dominant negative mutations in BK and other ion channels have been described previously (28,(32)(33)(34)(35)(36), but this is the first time to our knowledge that the underling molecular mechanism has been revealed in such detail at the single channel level. For the G375R mutation heterozygous with WT, 85% of the expressed channels were heteromeric, and all these heteromeric channels displayed toxic properties (Figs.…”
Section: Discussionmentioning
confidence: 84%
“…A dominant-positive effect is an analogy 33 to the well-known dominant-negative effect observed for some types of protein complexes and channelopathies 33,[44][45][46][47][48][49] Both can cause disease: dominant positive from a GOF and dominant-negative from complete or partial LOF, and both have a disproportionate fraction of the channels affected.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, variants in Na v 1.7, which resulted in an alteration of the channel function when expressed alone, were rescued by their interaction with the WT α-subunits [28]. Very recently, the group of Dr. Kucera modeled the interactions between Na v channels in order to examine their consequences on channel kinetics and confirmed that, if the question remains open how variants interacting with WT channels affect the Na + current, the condition where a variant channel potentiates the current generated by the WT leading to a gain of function, is conceivable [29].…”
Section: Dysfunctional Channels Cooperated With Wt and With Each Othe...mentioning
confidence: 99%